Personal Branding Puan Maharani Pada Akun Instagram @Puanmaharaniri Menuju Pemilihan Presiden 2024 - Jamil, Husnul; Hamad, Ibnu; Sari, Yunita (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research aims to analyze how Puan Maharani's personal branding on the Instagram account @Puanmaharaniri approaches the 2024 presidential election. This research uses a qualitative approach using the qualitative content analysis method based on the constructivist paradigm. Data collection was carried out using observation and documentation techniques and using three stages in analyzing the data, namely: data collection/reduction, presentation, and verification/conclusion. The research results show that the strategy for creating Puan Maharani's personal branding on the @puanmaharaniri Instagram account ahead of the 2024 presidential election was built by creating interesting content through the Instagram account with the tools used in personal branding on the @puanmaharani Instagram account, namely first, text; second, short videos; and third, photos. The concept of creating personal branding built by Puan Maharani through her Instagram account includes eight personal branding concepts by Peter Montoya. Some of Puan Maharani's branding that dominates in the formation of personal branding on her Instagram account are concern for small communities (little people), gender equality, and leadership. The overall branding built by Puan has not been able to increase her electability due to inconsistency in one strong branding attached to Puan Maharani, so that she becomes a figure known for this branding.